Oblicz w pamięci:
a) 7·(-9)=
b) (-8) j 1/2=
c) (-10)· 1,4=
d) (-1/3) · (-6)=
e) (-12) : 3=
f) 8,2 : (-2)=
g) 0,6 · (-9)=
h) (-8) · (-1/4)=
i) (-6):(-2)=


Odpowiedź :

Odpowiedź:

A)  -63

B)  -4

C)  -14

D)   2

E)   -4

F)   -4,1

G)  -5,4

H)   2

I)     3

Szczegółowe wyjaśnienie:

Odpowiedź:

a) 7·(-9)=-63

b) (-8) : 1/2=-16; (-8) • 1/2=-4 (źle napisałeś w pytaniu, więc podałem dwie opcje)

c) (-10)· 1,4=-14

d) (-1/3) · (-6)=2

e) (-12) : 3= -4

f) 8,2 : (-2)=-4,1

g) 0,6 · (-9)=-5,4

h) (-8) · (-1/4)=2

i) (-6):(-2)=3

Wyjaśnienie

Prosta regułka

+ i + daje +

+ i - daje -

- i - daje +

Liczę na naj <3